Inter-relationship between Geology, Soil and Vegetation of Kanasar Range in Chakrata Division of Uttar Pradesh - Raina, A. K.; Pharasi, S. C.; Prasad, K. G. (Indian Forester, 1994)
A general relationship between geology, soil and vegetation in the Kanasar Range of Chakrata Forest Division, Uttar Pradesh was evaluated. Geologically the rocks of the study site are of Pre-Cambrian to early Paleozoic in age with recent and subrecent deposits. Soils belongs to Typic Paleudoll (Konain series), Typic Argiudoll (Deoban series), Typic Paleudult (Kanasar series) and Humic Hapludult (Budher series) and all these polypedons are members of fine loamy, mixed, messic family. Vegetation of the study area is a climatic climax and falls under 12/C-Himalayan moist temperate forests. The study revealed that basal area of Cedrus deodara increased with increasing calcite content and decreased with increasing dolomite content. The study further indicated that relief and age acting on geology of Kanasar Range govern the existing soil whereas effect of altitude and climate on geology gives rise to natural vegetation. Climate and aspect on a particular site have given rise to existing floristic composition and also different pedogenic processes active at the site.